Electronic and quantum transport properties of a graphene-BN dot-ring hetero-nanostructure. (3rd April 2018) - Seel, Max; Pandey, Ravindra
Abstract: Quantum dots, quantum rings, and, most recently, quantum dot-ring nanostructures have been studied for their interesting potential applications in nanoelectronic applications. Here, the electronic properties of a dot-ring hetero-nanostructure consisting of a graphene ring and graphene dot with a hexagonal boron nitride (h-BN) ring serving as barrier between ring and dot are investigated using density functional theory. Analysis of the character of the wave functions near the Fermi level and of the charge distribution of this dot-ring structure and calculations of the quantum transport properties find asymmetry in the conductance resonances leading to asymmetric I–V characteristics which can be modified by applying a negative voltage potential to the central graphene dot.